The effect of ergonomics and psychosocial risk factors on musculoskeletal complaints and psychological health among fire fighters - Zainuddin, Nurul Farha (2014)
Fire fighters were exposed to ergonomics risk factors and psychosocial risk factors when acting as rescuers to victims of natural disasters, fires and accidents. These events would eventually lead to health-related problems such as musculoskeletal complaints and psychological health. Hence, the purpose of this research is to study the effect of ergonomics risk factors and psychosocial risk factors on the musculoskeletal complaints and psychological health among fire fighters. The total respondents participated in this study were 184. A self-administered questionnaire was used for data collection. The questionnaire consists of ergonomics risk factors which assessed by Dutch Musculoskeletal Questionnaire (DMQ) and psychosocial risk factors was employed the Job Content Questionnaire (JCQ). Meanwhile, musculoskeletal complaints were evaluated by adapted Standardized Nordic Questionnaire (SNQ) and psychological health was measured by General Health Questionnaire (GHQ-12). The results from multiple logistic regression indicated that not enough room at above to perform work properly significantly affect the development of neck complaints. Meanwhile, lifting a load that is hard to hold and slip or fall during work significantly affects the development of shoulder and back complaints. Other risk factor such as difficulty in exerting enough force because of uncomfortable postures was found to be significantly affecting the development of back complaints. As for the psychosocial risk factors, the psychological demand showed significant effect on lower limb. Findings from this study suggested for future research should consider for bigger respondent. As for the organization, the Fire Department should be more aware of the importance of physical fitness and being mentally strong to deal with any stressful condition that may occur during firefighting and rescue.